Educational aspects in the work of a teacher of vocational subjects (on the example of technicians training in the profession of hotel management technician) - Katarzyna Pardej (Jan Dlugosz University, 2022)
The article discusses educational aspects in the work of a teacher of vocational subjects in technical schools training for the profession of hotel management technician. The results of own research are presented, in which the research problem was formulated in the form of the question: how do teachers of vocational subjects in hotel technical schools perform the educational function? The research was qualitative in nature. Nine teachers of vocational subjects (teachers of theoretical vocational subjects and a teacher of practical vocational training) from two schools participated in it. During the research, the interview method and document analysis method were used. From the educational and preventive programs in effect at the studied schools, educational goals and a description of the student graduating from the technical school were obtained. An analysis was made of the extent to which they are implemented during lessons in vocational subjects.